Cover Feature: Covalent Inhibition in Drug Discovery (ChemMedChem 9/2019). (6th May 2019) - Ghosh, Avick Kumar; Samanta, Indranil; Mondal, Anushree; Liu, Wenshe Ray
Abstract : The Cover Feature shows notable covalent inhibitors and structures of their complexes with protein targets. Covalent inhibitors involve mainly electrophilic functional groups to form covalent adducts with nucleophilic amino acid residues in protein targets. These functional groups include electrodeficient alkene, nitrile, lactone, lactam, expoxide, alkylhalide, etc.. A notable exception are thiol‐containing compounds that are redox active to conjugate to cysteines in proteins. More information can be found in the Review by Wenshe Liu et al. onpage 889 in Issue 9, 2019 (DOI:10.1002/cmdc.201900107 ).